Ethanolic extract from Sophora moorcroftiana inhibit cell proliferation and alter the mechanical properties of human cervical cancer - Manli Guo; Dingcheng Guo; Lingzi Liao; Xiao Zhang; Zhilong Wang; Qiaozhen Zhou; Ping Chen; Ruiping Li; Bing Han; Guangjie Bao; Baoping Zhang (BMC, 2024)
Abstract Background Cervical cancer is one of the most common gynecological malignancies. Previous studies have shown that the ethanol extract of Sophora moorcroftiana seeds (EESMS) possesses an antiproliferative effect on several tumors in vitro. Therefore, in this study, we assessed the impact of EESMS on human cervical carcinoma (HeLa) cell proliferation. Methods The proliferation and apoptotic effects of HeLa cells treated with EESMS were evaluated using 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assay, dual acridine orange/ethidium bromide double staining, flow cytometry, and western blotting. Single-cell level atomic force microscopy (AFM) was conducted to detect the mechanical properties of HeLa cells, and proteomics and bioinformatics methods were used to elucidate the molecular mechanisms of EESMS. Results EESMS treatment inhibited HeLa cell proliferation by blocking the G0/G1 phase, increasing the expression of Caspase-3 and affecting its mechanical properties, and the EESMS indicated no significant inhibitory effect on mouse fibroblasts L929 cell line. In total, 218 differentially expressed proteins were identified using two-dimensional electrophoresis, and eight differentially expressed proteins were successfully identified using matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry. The differentially expressed proteins were involved in various cellular and biological processes. Conclusion This study provides a perspective on how cells change through biomechanics and a further theoretical foundation for the future application of Sophora moorcroftiana as a novel low-toxicity chemotherapy medication for treating human cervical cancer.